Comparison of Extraction Efficiency of Aqueous and Methanolic Extracts from Plant Tissues and Callus Cultures of Calotropis procera and Calotropis gigantea (Plant Tissue Culture and Biotechnology, 2017)
Extracts of plants may contain bioactive substances which could be used as natural antimicrobial agents against many microbes. Callus from the leaf material of Calotropis procera and C. gigantea was raised on different hormonal combinations and different extracts i.e. 50% methanolic, 90% methanolic and aqueous extracts of leaf and callus were prepared. The extraction efficiency of different extracts of plant tissue and callus was calculated and compared. Callus tissue is advantageous over plant tissues for extraction of phyto‐constituents for the basic reason that purification and isolation of active constituents are easier and also scale up strategies can be applied in vitro. Moisture content of tissue and the callus were analyzed and improved extraction efficiency was calculated after subtracting the moisture content.Plant Tissue Cult. & Biotech. 27(2): 171-180, 2017 (December)